PERSPEKTIF PENGEMBANGAN INDUSTRI GULA DI INDONESIA - KURNIA SUCI INDRANINGSIH; A. HUSNI MALIAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Sugar cane planted-area in Java is limited and supply of raw material forsugar companies (PG) is possible through improvement of sugar cane productivityand sugar content. It is necessary to implement individual sugar content or minimalsugar content guarantee between farmers’ group and PG’s management. PGexpansion to uotside Java (Sumatera, Sulawesi, Maluku and Papua) is urgent, at least15 new PG, in order to lessen dependence on sugar production from Java Island. PGlocated outside Java are designed not to produce sugar only, but also to makederivative products such as ethanol, alcohol, etc. Revitalizing research anddevelopment activities is necessary to generate new technology.